Penerapan Standar Akuntansi Keuangan Syariah pada Koperasi Jasa Keuangan Syariah : (Studi pada KSPPS BTM Bimu di Kota Bandar Lampung) - Efrida Efrida; Lisa Haji Diana; Muhammad Akbar Aldinata; Anas Malik (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
Descriptive analysis of the implementation of sharia financial accounting standard reports of BTM BiMU Bandar Lampung is presented in this paper. Accounting principles related to the presentation of financial statements in accordance with PSAK 101 concerning sharia financial statements and recognition, measurement, presentation, and disclosure of murabahah transactions based on PSAK 102 concerning mudharabah are the subject of the study. KSPPS BTM Bimu Bandar Lampung City is the target of the study. The qualitative methodology and primary data used in this study were obtained from BTM BiMu. The results of the study indicate that KSPPS BTM Bimu has not implemented accounting procedures in accordance with sharia PSAK.